1988
DOI: 10.1002/joc.3370080207
|View full text |Cite
|
Sign up to set email alerts
|

The synoptic climatology of ablation on a New Zealand glacier

Abstract: Local scale ablation and energy budget measurements are reported for the Ivory glacier in the Southern Alps of New Zealand over 53 days during two consecutive summer periods. Ablation averaged 38 mm day-', but varied from less than 10 mm day ~ I to over 70 mm day I . Radiation supplied 52% of the energy for glacier melt, with the convective fluxes contributing most of the remainder. The results are related to large scale synoptic weather patterns over the southwest Pacific region. Different synoptic situations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 18 publications
(12 reference statements)
8
80
0
Order By: Relevance
“…Measured average mass loss was approximately 40 mm w.e. d −1 , which is very similar to that measured by Hay and Fitzharris (1988) on the Ivory Glacier over two summer periods at a similar elevation (38 mm w.e. d −1 ).…”
Section: Degree-day Modelsupporting
confidence: 85%
See 2 more Smart Citations
“…Measured average mass loss was approximately 40 mm w.e. d −1 , which is very similar to that measured by Hay and Fitzharris (1988) on the Ivory Glacier over two summer periods at a similar elevation (38 mm w.e. d −1 ).…”
Section: Degree-day Modelsupporting
confidence: 85%
“…On other glaciers in the Southern Alps, Anderton and Chinn (1978) and Hay and Fitzharris (1988) found radiative heat to be the most important source of ablation (on the Ivory Glacier between 1400 and 1800 m a.s.l.). Recent energy and mass balance modelling of Brewster Glacier over the period 2004-2008 by Anderson et al (2010), using primarily meteorological data not collected on the glacier, showed that 48% of energy available for melt is sourced from net all-wave radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During periods confined to melting, R NET is the largest source of energy for ablation (88 W m -2 ), accounting for 64% of QM (Table 4), which is larger than previously reported (e.g. Hay and Fitzharris, 1988b;Gillett and Cullen, 2011). The main contributor to R NET during melt (QM > 0) is SW NET , which is sensitive to changes in surface albedo and variability in cloud conditions .…”
Section: Comparison To Other Multi-annual Glacier Climate Recordsmentioning
confidence: 76%
“…We use a degree day factor of 4.5 mm day-1 deg-1 as was derived for Franz Josef Glacier in the central Southern Alps (Anderson, 2003). H S is ablation from latent heat (rain on snow) which contributes ∼2% to annual ablation in the Southern Alps (Hay and Fitzharris, 1988). We tested the model by predicting ablation at the present ELA where annual snowfall is 4432 mm and no net accumulation occurs (mass balance 0).…”
Section: Temperature Effects On Snow Mass Balances In the Southern Alpsmentioning
confidence: 99%